CHILDREN AND VIOLENCE - Cunningham, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is organized around three general themes: 1) an introductory overview of the topic of violence, including theoretical background and cultural and structural factors; 2) an analysis of children and violence-related issues, including family, street, and school-based causes and consequences; and 3) consideration of prevention and interventions strategies as well as relevant policy implications. We will view violence both as a social phenomenon and as a lived experience.